Innovative reduced graphene oxide/polycysteine/coper titanate composite coating for corrosion-resistant and antibacterial tinplate in food packaging - A Priyadharshini; Joseph Raj Xavier (Results in Engineering)
This study describes the creation and viability evaluation of a new nanocomposite encasing for tinplate, specifically designed for alimentary packaging needs requiring excellent durability and protection. The coating system uses an epoxy resin matrix augmented with a ternary nanocomposite of rGO, PC, and CuTiO3. In this formulation, copper titanate nanoparticles are first functionalized with polycysteine and then anchored onto the surface of rGO, forming a hybrid nanostructure. This rGO/PC/CuTiO3 composite is subsequently integrated into the epoxy resin to fabricate the final coating. The addition of the nanocomposite greatly improves the physical features of the coated tinplate, especially increased tensile rigidity and elasticity, both of which are crucial for the mechanical requirements of food packaging. Moreover, polycysteine imparts inherent antimicrobial activity, helping to inhibit microbial growth and thereby extend the shelf life of packaged products. Electrochemical impedance spectroscopy (EIS) results demonstrate a remarkable increase in corrosion resistance, with the nanocomposite-coated tinplate exhibiting a coating resistance (Rcoat) of 3.55 × 1013 Ω.cm2 substantially higher than that of the conventional epoxy coating. Mechanical testing further confirms the enhanced structural robustness of the coating. Overall, the epoxy/rGO/PC/CuTiO3 nanocomposite coating offers a multifunctional solution for food packaging, combining mechanical integrity, excellent corrosion resistance, and antimicrobial protection. This innovative coating system holds great promise for advancing the performance, safety, and longevity of metal-based food packaging materials.